2022
DOI: 10.3390/vaccines10050705
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Knowledge towards COVID-19 Vaccine Hesitancy among a Subpopulation of Adults in Kenya: An English Survey at Six Healthcare Facilities

Abstract: Background: Vaccine hesitancy, as defined by the WHO, is the reluctance or refusal to vaccinate despite the availability of vaccines and is one of the ten threats to global health in 2019. Vaccine hesitancy remains a complex matter influenced by multiple factors, especially in sub-Saharan Africa. Methods: We conducted a cross-sectional study between November 2021 and January 2022 among the general adult public seeking care at six different healthcare facilities in Kenya. The survey, in English, consisted of qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
2
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
4
17
2
1
Order By: Relevance
“…This has also been estimated by other studies, including the study by Orangi et al (2021) who found that non-refugees in rural settings were 2.5 times more likely to be vaccination hesitant than those in urban settings [5]. Among other reasons, this may be due to poor access and poor awareness [17].…”
Section: Plos Global Public Healthsupporting
confidence: 72%
“…This has also been estimated by other studies, including the study by Orangi et al (2021) who found that non-refugees in rural settings were 2.5 times more likely to be vaccination hesitant than those in urban settings [5]. Among other reasons, this may be due to poor access and poor awareness [17].…”
Section: Plos Global Public Healthsupporting
confidence: 72%
“…[1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] .…”
Section: Uncited Referencesunclassified
“…Previous research has also highlighted the importance of the media in Kenya, showing healthcare workers and media as the top trusted sources for government and faith-based organizations (Shah et al, 2022). The information received from media sources consisted mainly of COVID-19 vaccine availability and eligibility.…”
Section: Discussionmentioning
confidence: 99%